The Development and Validation of the Appreciative Intelligence® Scale. Issue 2 (26th May 2020) - Whitaker, Brian; Thatchenkery, Tojo; Godwin, Lindsey N.
ABSTRACT: While Appreciative Intelligence® – the capacity to reframe and see the potential in any situation and act on it with success – has generated a robust body of literature, scholarly advancement of this construct has been hampered by the lack of a validated instrument. Over two studies, we develop the Appreciative Intelligence® Scale (AIS), a 26-item survey organized into six factors. Study 1 explores the factor structure of the AIS using EFA. Study 2 uses hierarchical confirmatory factor analysis (HCFA) and hierarchical regression analyses to provide evidence for its convergent, discriminant, and criterion-related validity. The results support the priori six-factor structure of the AIS, indicating it is a valid measure of Appreciative Intelligence® useful in predicting proactive behavior at the individual, team, and organizational levels.